Reconsideration of the use of meningococcal polysaccharide vaccine. - Granoff, D; Pollard, A (2007)
In 2005, a quadrivalent meningococcal conjugate vaccine was licensed in the United States for persons aged 11-55 years of age. For children aged 2-10 years with underlying diseases associated with increased risk of meningococcal disease, unconjugated meningococcal polysaccharide (MPS) vaccination is still recommended. This article reviews the increasing evidence that MPS vaccination impairs serum anticapsular antibody responses to subsequent injections of MPS or meningococcal conjugate vaccines (antibody hyporesponsiveness). Administering MPS as a probe to assess conjugate vaccine-induced immunologic memory also can extinguish subsequent memory anticapsular antibody responses, whereas conjugate vaccination regenerates memory B cells. Whether induction of antibody hyporesponsiveness or loss of immunologic memory increase the risk of acquiring meningococcal disease remains speculative. However, for children at increased risk of meningococcal disease, immunization with meningococcal quadrivalent conjugate vaccine off-label instead of MPS vaccine should be considered. Requirements for licensure of new glycoconjugate vaccines that include performing comparative clinical trials to demonstrate noninferiority with MPS vaccine, or use of a MPS challenge to assess conjugate-induced immunologic memory also should be modified because there are safer approaches for obtaining the same information.